2022
DOI: 10.3390/land11071004
|View full text |Cite
|
Sign up to set email alerts
|

Study on Ecological Loss in Coal Mining Area Based on Net Primary Productivity of Vegetation

Abstract: Opencast mining contributes to the severe disturbance of vegetation and serious damage to the ecological environment. Scientific assessment of the ecological losses may provide guidance for the sustainable land use in mining areas. This study uses the Carnegie Ames Stanford Approach (CASA) model to estimate the net primary productivity (NPP) of vegetation in the Pingshuo mining area from 2006 to 2020 and uses statistical analysis and mathematical models to study the impact of mining and land reclamation on NPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
(57 reference statements)
0
0
0
Order By: Relevance
“…The natural law of slow development and changes in the vegetation and other ecological elements makes long-term monitoring necessary. Ecological restoration projects generally have management periods of 1-3 years after completion [52,53]; however, due to the previously discussed long-term impacts of ground deformation on the vegetation, it was found that the changes in the vegetation under the long-term impacts may take 10 or even 20 years to be reflected [54,55], which is mainly determined by the time required for the succession of the plant communities [56][57][58]. The conflict between the laws of nature and the requirements of reality has resulted in many projects paying too much attention to the short-term effects of the repairs.…”
Section: Suggestions For the Supervision Of Revegetation In The Under...mentioning
confidence: 99%
“…The natural law of slow development and changes in the vegetation and other ecological elements makes long-term monitoring necessary. Ecological restoration projects generally have management periods of 1-3 years after completion [52,53]; however, due to the previously discussed long-term impacts of ground deformation on the vegetation, it was found that the changes in the vegetation under the long-term impacts may take 10 or even 20 years to be reflected [54,55], which is mainly determined by the time required for the succession of the plant communities [56][57][58]. The conflict between the laws of nature and the requirements of reality has resulted in many projects paying too much attention to the short-term effects of the repairs.…”
Section: Suggestions For the Supervision Of Revegetation In The Under...mentioning
confidence: 99%